2020
DOI: 10.1111/ppa.13195
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus identification and thiophanate‐methyl sensitivity of Colletotrichum gloeosporioides species complex associated with fruit with symptoms and symptomless leaves of mango

Abstract: Colletotrichum spp. are known causal agents of anthracnose in a broad host range, causing severe losses. Currently, the most effective way to reduce disease is by fungicide application, which could give rise to resistant populations. This study aimed to determine the Colletotrichum species present in conventional and organic mango orchards and to evaluate their pathogenicity and sensitivity to the benzimidazole fungicide thiophanate‐methyl. Seventy‐one isolates from fruit with symptoms and symptomless leaves w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In order to control fungus and ensure the high quality and high yield output of agricultural products, pesticides are widely used in agricultural production activity [ 31 ]. In fruit and vegetable fields, TM is often used to prevent and control various diseases in crops, as well as for postharvest food storage and preseed planting treatment [ 32 , 33 ]. Studies have shown that long-term exposure to TM can pose high risks to human health due to its potential genotoxicity, neurotoxicity, reproductive toxicity and teratogenicity [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to control fungus and ensure the high quality and high yield output of agricultural products, pesticides are widely used in agricultural production activity [ 31 ]. In fruit and vegetable fields, TM is often used to prevent and control various diseases in crops, as well as for postharvest food storage and preseed planting treatment [ 32 , 33 ]. Studies have shown that long-term exposure to TM can pose high risks to human health due to its potential genotoxicity, neurotoxicity, reproductive toxicity and teratogenicity [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…C . chrysophilum was recently isolated and described in Brazil from anthracnose in bananas (Vieira et al ., 2017) and was found to be associated with anthracnose on mango in Mexico (Fuentes‐Aragón et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the diversity of Colletotrichum species associated with a host is crucial for the implementation of efficient management strategies because some species are better adapted than others in the field. Habituation of some Colletotrichum species is enhanced by factors such as high or inherent resistance to fungicides (Chen et al ., 2018; Fuentes‐Aragón et al ., 2020), the development of sexual morphs that are epidemiologically important for genetic recombination, or virulence grades (Sharma et al ., 2017; De Silva et al ., 2019; Fuentes‐Aragón et al ., 2020). In addition, monitoring quarantined pathogens requires precise identification to avoid spreading (Weir et al ., 2012; Crous et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…11 For example, thiophanate and thiophanate-methyl containing two thiourea units are broad-spectrum systemic fungicides that could effectively protect plants from the pathogen fungi. 12,13 The thiourea-based insecticides, such as diafenthiuron, chloromethiuron and buprofezin, are used for the control of insect pests on crops. [14][15][16] The rodenticide antu possesses a simple chemical structure, consisting of naphthalene combined with a thiourea scaffold.…”
Section: Introductionmentioning
confidence: 99%